Trinuclear and Mononuclear Lanthanoid Complexes Containing 2‐Methyl‐8‐quinolinolate: Synthesis, Structures, and Magnetic Properties. Issue 20 (21st May 2019) - Ghazali, Nurul F.; Phonsri, Wasinee; Murray, Keith S.; Junk, Peter C.; Deacon, Glen B.; Turner, David R.
Abstract : Two series of new lanthanoid complexes containing 2‐methyl‐8‐quinolinolate (MQ – ) have been prepared at elevated temperatures. Lighter elements yield trinuclear complexes [Ln3 (MQ)9 (HMQ)]· 5H2 O· 3MeOH (1Ln, where Ln = Pr, Eu, Gd, Tb, Dy and Ho) by solvothermal reactions, and heavier lanthanoids yield the mononuclear complexes [Ln(MQ)3 (HMQ)]· HMQ· MeOH (2Ln, where Ln = Dy, Ho, Er and Yb), with overlap between the two series found in the cases of Dy and Ho. Magnetic studies reveal that1Tb, 1Dy, and2Er show distinct slow magnetic relaxation under external DC fields. The magnetic data for1Gd yielded the J value for weak antiferromagnetic coupling and the magnetocaloric –Δ S m value of 20 J kg –1 K –1 at 2 K and Δ H = 5 T. Abstract : Two series of new lanthanoid complexes containing 2‐methyl‐8‐quinolinolate, [Ln3 (MQ)9 (HMQ)] (Ln = Pr–Ho) and [Ln(MQ)3 (HMQ)] (Ln = Dy–Yb), have been synthesized with a structural overlap at Dy and Ho. Distinct slow magnetic relaxation is observed for the trinuclear terbium and dysprosium complexes and the mononuclear erbium complex.